2021
DOI: 10.1002/jbt.22774
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporosis effect of geraniin on ovariectomy‐induced osteoporosis in experimental rats

Abstract: Osteoporosis is a skeletal condition that is characterized by decreasing bone density and deteriorating bone mass. The plant-based phytoconstituent such as geraniin possesses better therapeutic potentials in biomedical field. In the current experimental study, we planned to scrutinize the therapeutic potential of geraniin against ovariectomy (OVX)-induced osteoporosis in rats and find the possible mechanism.Healthy Sprague Dawley rats were randomized into six groups and subjected to geraniin and alendronate (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Ovariectomized rodents are very useful animal models to study geriatric diseases. For example, ovariectomy is a frequently used technique to induce osteoporosis in rodent models (17)(18)(19). Rodrigues et al (20) found that physical exercise could alter the morphology of the liver of ovariectomized Ldlr -/mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovariectomized rodents are very useful animal models to study geriatric diseases. For example, ovariectomy is a frequently used technique to induce osteoporosis in rodent models (17)(18)(19). Rodrigues et al (20) found that physical exercise could alter the morphology of the liver of ovariectomized Ldlr -/mice.…”
Section: Introductionmentioning
confidence: 99%
“…Ovariectomized rodents are very useful animal models to study geriatric diseases. For example, ovariectomy is a frequently used technique to induce osteoporosis in rodent models ( 17 19 ). Rodrigues et al.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory immune response occurs through activation of immune cells which secreted proinflammatory cytokines, such as TNF-α, IL-1α and IL-6. Experimental and clinical studies have been indicated that TNF-α, IL-1α and IL-6 are cytokines associated with infection, trauma, and sepsis syndrome (4,20). TNF-α starts and, regulates cytokinesis cascade during the inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that cod bone gelatin treatment can positively affect bone improvement by suppressing the release of TNF-α, IL-1 and IL-6, which often increases post-OVX (37). Many studies revealed the anti-inflammatory effects of curcumin, vanillic acid, soybean, geraniin, vicenin in the OVX rats (5,16,20). In this study, we used BA to test the anti-inflammatory effect against the inflammatory changes associated with OVX.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, selected flavonoids were shown to induce osteoblastic differentiation and to inhibit osteoclastogenesis [ 14 , 15 , 16 , 17 ]. Flavonoids were also reported to induce several anti-OS activities, including cell cycle arrest, induction of apoptosis and inhibition of invasion and metastasis, suggesting a therapeutic potential [ 18 , 19 , 20 , 21 , 22 , 23 ]. Concerning current OS therapy, the anthracycline doxorubicin (Dox) is the most commonly prescribed agent to treat this cancer.…”
Section: Introductionmentioning
confidence: 99%